Mizumi: Digital Sports Centre - Busang, Trevor Roma (Trends in Undergraduate Research, 2023)
Digital sport is the product of merging electronic technology into sport activities. It is a new generation of social activitise that can be integrated online and globally regardless of where you are. Based on the popular animated series Pokemon, the concept is to have multiple areas with different activities engaging with the target users around the area. The phrase "catch-em-all" usde to refer to the intention to capture the surrounding people and creating a new interactive area for the anime fans. The buildings are divided by three to resemble the three legendary Pokemon Lake Guardians. The spaces are also planned according to the gym leader theme from the game adapted from the anime.